2003
DOI: 10.1111/j.1745-9125.2003.tb01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Police, Minorities, and the French Republican Ideal*

Abstract: This paper examines the strained relationship between French police agencies and ethnic minorities and discusses evidence of ethnic discrimination by the police and the criminal justice system. Until recently, the idea that ethnic composition of a police force ought to reflect, to some degree, the community it polices, seemed odd in France. We argue that there are two main reasons for this viewpoint: first, a conception of the role of the police in the State as accountable to the government rather than to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…While the constraints of our data limited possible analyses, we believe our data suggest the need for more work examining the role of income and community level attitudes on racially disproportionate arrests, as well as changes in policing and economic policies as well as neighborhood demographics over time. Our findings are similar to prior research around the world that has shown that ethnic minorities and other marginalized cultural groups are often disproportionately targeted by narcotics policing, irrespective of differentials in narcotics use (2, 7, 17-19). We build upon that work by suggesting that this disproportion varies by neighborhood, and that biased policing practices may play a role in maintaining or promoting racial segregation within and between neighborhoods.…”
Section: Discussionsupporting
confidence: 89%
“…While the constraints of our data limited possible analyses, we believe our data suggest the need for more work examining the role of income and community level attitudes on racially disproportionate arrests, as well as changes in policing and economic policies as well as neighborhood demographics over time. Our findings are similar to prior research around the world that has shown that ethnic minorities and other marginalized cultural groups are often disproportionately targeted by narcotics policing, irrespective of differentials in narcotics use (2, 7, 17-19). We build upon that work by suggesting that this disproportion varies by neighborhood, and that biased policing practices may play a role in maintaining or promoting racial segregation within and between neighborhoods.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, proponents of ethnic diversification of police argue that such policies may have the potential to reduce ongoing tensions between police and residents within ethnically underrepresented communities whose cultural backgrounds are extremely divergent from those in political power (Weitzer & Hasisi, 2008). This evidence has been produced in Northern Ireland (Weitzer, 1995), Zimbabwe (Weitzer, 1990), Israel (Hasisi, 2008;Weitzer & Hasisi, 2008) and France (Zauberman & Levy, 2003). Thus, in the case of the present study, the evidenced attitude change among all LAPD officers in 2007 -and particularly among Caucasian officers -may have been due, in part, to LAPD's traditional policing culture having been transformed through ethnic diversification into a representative bureaucracy.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 94%
“…The French mass media have responded to these local and other global developments by insisting that the banlieues are not only rife with criminality but contain strong elements of Islamic fundamentalism and possible tendencies to terrorist activity (Laachir 2007). The economic downturn of the late 20th Century had already resulted in a tightening of immigration laws and the much‐resented intensification of police identity checks (Zauberman and Levy 2003). However, following the success of the centre right in the 2002 French general election, the new Minister of the Interior, Mr Nicolas Sarkozy, responded to such media alarmism by lowering the age of penal responsibility from 13 to ten years and introducing a ‘zero tolerance’ approach to such ‘quality of life crimes’ as loitering in public housing stairwells and hallways, begging, or defrauding public transport.…”
Section: The French Riots Of 2005mentioning
confidence: 99%